2019
DOI: 10.7554/elife.50253
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical diversification of the receptor-ligand interaction controlling self-incompatibility in Arabidopsis

Abstract: How two-component genetic systems accumulate evolutionary novelty and diversify in the course of evolution is a fundamental problem in evolutionary systems biology. In the Brassicaceae, self-incompatibility (SI) is a spectacular example of a diversified allelic series in which numerous highly diverged receptor-ligand combinations are segregating in natural populations. However, the evolutionary mechanisms by which new SI specificities arise have remained elusive. Using in planta ancestral protein reconstructio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 74 publications
0
15
1
Order By: Relevance
“…At Alr2, for example, a single mutation generated an allele encoding a novel binding specificity that would likely allow the animal carrying it to distinguish itself from an animal carrying the ancestral allele. In contrast, at self-incompatibility loci, which encode coevolving pairs of interacting proteins, sequential mutations in both proteins are thought to be required for them discriminate between themselves and other alleles (Chantreau et al, 2019;Chookajorn et al, 2004). This constraint may require self-incompatibility alleles to evolve through non-functional intermediates (Bod'ova et al, 2018;Uyenoyama et al, 2001), something we did not observe here.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…At Alr2, for example, a single mutation generated an allele encoding a novel binding specificity that would likely allow the animal carrying it to distinguish itself from an animal carrying the ancestral allele. In contrast, at self-incompatibility loci, which encode coevolving pairs of interacting proteins, sequential mutations in both proteins are thought to be required for them discriminate between themselves and other alleles (Chantreau et al, 2019;Chookajorn et al, 2004). This constraint may require self-incompatibility alleles to evolve through non-functional intermediates (Bod'ova et al, 2018;Uyenoyama et al, 2001), something we did not observe here.…”
Section: Discussioncontrasting
confidence: 51%
“…Most work on the evolution of new self-recognition alleles has focused on multi-component systems such as plant self-incompatibility loci, in which discrimination is controlled by linked genes encoding proteins that have co-evolved to interact (or not interact) with each other (Bod'ova et al, 2018;Chantreau et al, 2019;Chookajorn et al, 2004;Matton et al, 1999;Uyenoyama et al, 2001). In contrast, the evolution of new alleles in one-component systems has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…For the sporophytic model in Brassicaceae and the gametophytic models in the Solanaceae and Rosaceae, SI specificity is controlled by a single locus (the S-locus) that contains two closely linked genes expressed in pollen grains and in the style respectively (Takayama and Isogai 2005). Producing a new SI specificity requires changes in both genes, because any mutation affecting only one of the two genes will produce a self-compatible haplotype (Charlesworth and Charlesworth 1979;Uyenoyama et al 2001;Chantreau et al 2019). In the present study, prezygotic analyses based on stigma tests and postzygotic analyses based on paternity assignments revealed an asymmetrical compatibility behavior of [SC] individuals depending on whether they were considered as pollen recipients or as pollen donors.…”
Section: Sc Behavior In L Vulgare Involves An Si Breakdown In Pollenmentioning
confidence: 99%
“…A recent application of ASR in plants is the study of the ligand-receptor interactions in the self-incompatibility (SI) of Brassicaceae. This is a spectacular example of a diversified allelic series in which numerous highly diverged receptor-ligand combinations are segregating in natural populations [175] . Using in planta ancestral protein reconstruction, the study demonstrated that two allelic variants, segregating as distinct receptor-ligand combinations, diverged through an asymmetrical process whereby one variant has retained the same recognition specificity as their (now extinct) putative ancestor, while the other has functionally diverged and now represents a novel specificity no longer recognized by the ancestor.…”
Section: Evolution Of Protein Specificitymentioning
confidence: 99%